Peran Kepala Sekolah dalam Pembinaan Karakter Siswa di SMAK Gabriel Wanibesak - Melania Habu Lau (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2024)
The purpose of this study was to find out the role of the school principal in building student character at Gabriel Wanibesak High School, Lorotolus Village, Malaka District, Wewiku District, and the factors that support and hinder the role of school principals in building student character. This study used a qualitative method. Data collection techniques were carried out using observation, interviews, and documentation. The results of this study are as follows: First, the role of the principal at Gabriel Wanibesak High School as a leader and example for subordinates and all students of Gabriel Wanibesak High School. As a simple example shows, the two principals set a good example for all teachers, staff, and students. Always arriving on time to school, fostering, managing, and supervising school programs so they can run well, as evidenced by a teaching and learning process at school. The three school principals can perform additional roles as education managers, leaders, supervisors, and administrators. This proves that the principal's role in developing student character at SMAK Gabriel Wanibesak plays a good role.